Sink the Bismarck! [videorecording (DVD)] - Gilbert, Lewis, 1920-2018-; More, Kenneth, 1914-1982; Wynter, Dana; Möhner, Carl, 1921-2005; Naismith, Laurence, 1908-1992; Forester, C. S. (Cecil Scott), 1899-1966 (Fox war classics., 2003)
The Bismarck was the fabled German battleship of World War II. Traces the "life" of the Bismarck from its launching (courtesy of newsreel footage) through its many battles and narrow escapes, concluding with its far-from-inevitable sinking in the Spring of 1941. The story concentrates on the human element, specifically a British intelligence captain, who has lost his family in the London blitz and thus has a personal reason for seeing the Bismarck blasted from the sea. The captain's tireless efforts are abetted by the love and support of a female naval officer.